Mathematical modeling in basic education: the first experience lived - Derli Kaczmarek; Dionísio Burak (ACTIO: Docência em Ciências, 2018)
This paper aims to analyze the interactions between students and between student-teacher in the course of the development of a Modeling activity, making some notes regarding the first experience of the teacher with Modeling. The activities, developed with students of the ninth grade of Elementary School, are part of the master's dissertation of the author. The Burak references were used to conduct the activities with Modeling and Vygotsky to carry out the analyzes. The research, of a qualitative nature, analyzes the actions and interactions lived between all the subjects (students and teacher) in activities developed with the use of this methodology. The results show that the mathematical modeling reinforces the creation of social links, because it focuses on individual development in dynamic and dialectical aspect, and promotes the appearance of zone of proximal development, highlighting the principles of Vygotsky.